Holistic mobile game development with Unity : an all-In-one guide to implementing mechanics, art design, and programming for iOS and Android mobile games - de Byl, Penny, ....- (Burlington : Focal Press, 2015)
"Master mobile game design and development by simultaneously learning about the principles of art, design and code in this all-in-one guide to creating iOS and Android games in the cutting-edge game engine Unity. You'll gain multidisciplinary skills needed to succeed in the independent mobile games industry using Penny de Byl's holistic method and be up and running through hands-on exercises that will take you all the way from design to publishing in the Apple App Store and Google Play Store. - Over 70 practical step-by-step exercises recreating the game mechanics of contemporary mobile games including Angry Birds, Temple Run, Year Walk, Minecraft, Curiosity Cube, Fruit Ninja and more. - Design principles, art and programming in unison - the one-stop shop for indie developers requiring interdisciplinary skills in their small teams. - An introduction to essential two- and three-dimensional mathematics, geometry and physics concepts. - A portfolio of royalty free reusable game mechanics and assets. - Accompanying website, www.holistic3d.com, features project source code, instructional videos, art assets, author blog, and teaching resources. Challenge questions and lesson plans available online for an enhanced learning experience"--
Keywords: Unity (Electronic resource).; Computer games -- Programming; Games -- Video & Electronic; Mobile games